USULAN RANCANGAN SISTEM PELAKSANAAN DAN EVALUASI PELATIHAN DI PT PINDAD (PERSERO) - Cindy Anastasia Purb, Christine
PT Pindad (Persero) has a vision to become a leading global manufacturer of defense equipment in 2026. One of the efforts to achieve this vision is to have human resources that can compete and adapt in the industry 4.0 era, but the company does not have the human resources as expected. One of the reasons is that the company has not entered the 4.0 learning system. Therefore, the implementation of an LMS for the training implementation and evaluation is desired. Moreover, there are problems in the company in managing training, namely that it cannot be done online, which results in employees having limited time and distance in accessing training, training evaluations are often not done and evaluation results are often lost, and evaluation reports are not made. Based on the 5 Whys analysis done, it was concluded that the source of the problem is that the company's training implementation and evaluation system is done manually. Based on that, a solution is given, an automated training implementation and evaluation system, which is based on LMS. Therefore, this study aims to design an automated training implementation and evaluation system. The system design is created by using the FAST development method with a model-based approach that uses object modeling. The designing step begins with identifying the scope and problems, identifying the system requirements, modeling the system requirements, modeling objects, designing the user interface, and testing the system design. Through that step, company will get a training system design with an LMS in general, an automated training implementation and evaluation business process, and a training implementation and evaluation system prototype that has passed verification and validation. If it is implemented, the system prototype will be able to help company in implementing and evaluating training, communicating between users, and receiving inputs from employees. However, this prototype has not been able to be connected with the training activities planning documentation and has not been able also to run with several devices.